Bugs and bugsicles : insects in the winter - Hansen, Amy (Boyds Mills Press, 2010)
Every fall insects disappear, and every spring they return. Where do they go? The dragonfly dies, leaving its young safe in the muddy bottom of a stream. The monarch butterfly sails the air to dry mountains in Mexico. And the Arctic woolly bear caterpillar becomes a "bugsicle"--it freezes solid, then thaws out to live another day. The honeybee, praying mantis, field cricket, ladybug, and pavement ant also use awe-inspiring tricks to outwit the killing frosts of winter. The author and illustrator re-create the insects' movements and reveal their secrets.